PENGARUH KEPUASAN KERJA KARYAWAN, PRODUKTIVITAS, MOTIVASI TERHADAP KINERJA OUTSOURCING KARYAWAN YANTEK (PELAYANAN TEKNIK) DI PLN ULP BLORA - Damayanti, Anis Safitri (Universitas Nusantara PGRI Kediri, 2023)
This research aims to determine the effect of 1) job satisfaction on employee performance, 2) work productivity on employee performance, and 3) work motivation on employee performance. This type of research is quantitative research. The sampling technique used is a saturated sample. The sample for this research was all 38 employees of YANTEK PT PLN Blora. Data processing uses IBM SPSS Statistics 24 software. Data analysis techniques use validity and reliability test results, classical assumption test results, and hypothesis testing results. The research results show that partially job satisfaction has a positive and significant influence on employee performance, work productivity has a positive and significant influence on employee performance, motivation has a positive and significant influence on employee performance. Simultaneously, satisfaction, productivity and motivation of monkeys have a significant effect on employee performance.